Effect of Ultrasonic-Assisted Blanching on Size Variation, Heat Transfer, and Quality Parameters of Mushrooms - Lespinard, Alejandro Rafael (2015)
The main aim of this work was to assess the influence of the application of power ultrasound during blanching of mushrooms (60–90 °C) on the shrinkage, heat transfer, and quality parameters. Kinetics of mushroom shrinkage was modeled and coupled to a heat transfer model for conventional (CB) and ultrasonic-assisted blanching (UB). Cooking value and the integrated residual enzymatic activity were obtained through predicted temperatures and related to the hardness and color variations of mushrooms, respectively. The application of ultrasound led to an increase of shrinkage and heat transfer rates, being this increase more intense at low process temperatures. Consequently, processing time was decreased (30.7–46.0 %) and a reduction in hardness (25.2–40.8 %) and lightness (13.8–16.8 %) losses were obtained. The best retention of hardness was obtained by the UB at 60 °C, while to maintain the lightness it was the CB and UB at 90 °C. For enhancing both quality parameters simultaneously, a combined treatment (CT), which consisted of a CB 0.5 min at 90 °C and then an UB 19.9 min at 60 °C, was designed. In this manner, compared with the conventional treatment at 60 °C, reductions of 39.1, 27.2, and 65.5 % for the process time, hardness and lightness losses were achieved, respectively. These results suggest that the CT could be considered as an interesting alternative to CB in order to reduce the processing time and improve the overall quality of blanched mushrooms.